Characterization of water intake and water conversion ratio for male and female broilers from four commercial broiler lines reared to eight weeks of age - J.Z. Hiltz; C.W. Maynard; T.W. Tabler; M.A. Maqueda; K.M. Shafer; K.B. Nelson; M.T. Kidd; N.B. Anthony; S.K. Orlowski-Workman (Journal of Applied Poultry Research)
Summary: Increased interest and investigation into the sustainability of broiler production has led to a need for reliable and repeatable means to measure water intake and its conversion rate into salable meat. Therefore, a study was conducted to characterize the water intake and water conversion ratio (WCR) of male and female broilers from four modern broiler strains. Two of these lines represented fast growing broiler strains (FGB A and FGB B) targeting a small bird market and two represented high yielding broiler strains (HYB A and HYB B). Three replicates of 25 sexed broilers from each line were placed into 24 experimental pens and reared for an 8-week period. Broiler BW, feed intake, and water intake were monitored weekly and used to calculate feed conversion ratio (FCR) and WCR. Broilers were processed at 6 and 8 weeks of age for determination of carcass traits. Male broilers had higher water intakes throughout the experimental period. Strain significantly influenced broiler water intake and WCR throughout the experimental period, but these differences did not appear to be linked to broiler product type (i.e., fast growing or high yielding). Interactions between strain and sex were observed for water intake starting at week 4 and continuing through week 7. No interactions between strain and sex were observed for WCR. Water intake data and WCR reported herein serve to allow for baseline values derived from broilers serving the 2 major sectors of the broiler industry in literature and for future research.